2022
DOI: 10.3389/fphar.2022.826055
|View full text |Cite
|
Sign up to set email alerts
|

Salmon Calcitonin Exerts an Antidepressant Effect by Activating Amylin Receptors

Abstract: Depressive disorder is defined as a psychiatric disease characterized by the core symptoms of anhedonia and learned helplessness. Currently, the treatment of depression still calls for medications with high effectiveness, rapid action, and few side effects, although many drugs, including fluoxetine and ketamine, have been approved for clinical usage by the Food and Drug Administration (FDA). In this study, we focused on calcitonin as an amylin receptor polypeptide, of which the antidepressant effect has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Depression is a common debilitating neuropsychiatric disorder with an increased incidence year on year (Hammen, 2018). Our group has recently demonstrated that a single administration of sCT could ameliorate a depressive-like phenotype probably via the amylin signaling pathway (Jiang et al, 2022). The potential role of the calcitonin-AMYR axis in depression has been delineated by exploiting both agonists (e.g., sCT) and inhibitors/antagonists of AMYR (e.g., AC187; Hay et al, 2005;Jiang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Depression is a common debilitating neuropsychiatric disorder with an increased incidence year on year (Hammen, 2018). Our group has recently demonstrated that a single administration of sCT could ameliorate a depressive-like phenotype probably via the amylin signaling pathway (Jiang et al, 2022). The potential role of the calcitonin-AMYR axis in depression has been delineated by exploiting both agonists (e.g., sCT) and inhibitors/antagonists of AMYR (e.g., AC187; Hay et al, 2005;Jiang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has recently demonstrated that a single administration of sCT could ameliorate a depressive-like phenotype probably via the amylin signaling pathway (Jiang et al, 2022). The potential role of the calcitonin-AMYR axis in depression has been delineated by exploiting both agonists (e.g., sCT) and inhibitors/antagonists of AMYR (e.g., AC187; Hay et al, 2005;Jiang et al, 2022). However, the mechanism of its long-term action remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations